Decolonizing the Second World - Feldmann, Fanni (Hungarian Journal of English and American Studies, 2020)
Book review:Tlostanova, Madina. Postcolonialism and Postsocialism in Fiction and Art: Resistance and Re-existence. Cham: Palgrave Macmillan, 2017. xi + 224 pages. ISBN 978-3-319-48444-0. Hb. €88.39.